The Effect of Sodium Silicate (TX-85) as Liquid Based Stabilizer on Shear Strength of Batu Pahat Soft Clay (BPSC) - Mat Nor, Muhammad Salahuddin; Ahmad Tajudin, Saiful Azhar (Recent Trends in Civil Engineering and Built Environment, 2024)
Soft clay is one of the most difficult soils found in project development due to its high compressibility and swelling, as well as its restricted bearing capacity. All these problematic issues will directly affect the strength of the soil and cause difficulties for the operation of construction. For the current practices, mechanical stabilization such as compaction and soil replacement was used to increase the clayey soil's strength before starting construction work. However, it is not too practical to be used in terms of the construction time period and high cost. So, to overcome this issue, chemical stabilization was used to increase the soil's tensile strength. A new liquid stabilizing chemical with the commercial brand name "TX-85" was launched into the construction sector to improve the strength and reliability of soils for building and road construction. As a result, a laboratory study was carried out to see how Sodium Silicate affected the unconfined compressive strength of Batu Pahat Soft Clay (BPSC). According to the research that has been conducted, the optimum proportion of sodium silicate is 9%. Meanwhile, from the conducted compaction test, the value of maximum dry density (MDD) and optimum moisture content (OMC) were 1520 kg/m3 and 23% respectively. For the Atterberg limit of untreated samples, the obtained values of liquid limit, plastic limit, and plasticity index were 73%, 29.12%, and 43.88% respectively.   Keywords: Soft Clay, Unconfined compressive strength, Sodium Silicate